Analisis Pengaruh Hard Skill dan Job Involvement Terhadap Kinerja Pegawai Dinas Pertanian Kabupaten Asahan - Rangga Hadi Wijaya; Hilma Harmen (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the influence of hard skills and job involvement on the performance of employees at the Department of Agriculture in Asahan Regency. Hard skills are defined as abilities that include mastery of knowledge, technology, and technical skills required in the job, while job involvement refers to the extent to which an individual is engaged in their work, shows concern and attention towards it, and views their job as an important part of their identity and self-worth. This research employs a quantitative approach using multiple linear regression analysis. The sample consists of all employees at the Department of Agriculture in Asahan Regency, totaling 77 respondents. The results show that hard skills have a positive and significant effect on employee performance, with a beta value of 0.451 and a significance value of 0.000. Job involvement also has a positive and significant effect on employee performance, with a beta value of 0.526 and a significance value of 0.000. Simultaneously, these two variables contribute 35.2% of the variance in employee performance, while the remaining percentage is influenced by other variables.